Development of a coaching system for electrical stimulation rowing: a feasability study in able-bodied individuals - Tajali, S.; Fok, K. L.; Theventhiran, P.; Ye, G.; Yokoyama. H.; Nakagawa, K.; Masani, K. (Sensors, 2022)
Background: Functional electrical stimulation (FES) during rowing has substantial effects on cardiovascular health in individuals with spinal cord injuries. Currently, manual stimulation control where stimulation is operated by rowers is mostly utilized. However, it takes time to obtain the skill to initiate FES at the optimal timing. The purpose of this study was to develop a coaching system that helps rowers to initiate FES at the optimal timing. Methods: The optimal range for FES application was identified based on the electromyography of the left quadriceps in 10 able-bodied individuals (AB). Then, the effects of the coaching system on the timing of button-pressing, power, and work were investigated in 7 AB. Results: Vastus lateralis (VL) activation began consistently before the seat reached the anterior-most position. Therefore, seat position at the onset of VL was used as the variable to control the switch timing in the coaching system. The results revealed significantly higher power and work outputs in the coaching than the no-coaching condition (median power coaching: 19.10 W, power no-coaching: 16.48 W, p = 0.031; median work coaching: 109.74 J, work no-coaching: 65.25 J, p = 0.047). Conclusions: The coaching system can provide the optimal timing for FES, resulting in improved performance.